Sistem Pendukung Keputusan Persetujuan Pengajuan Kredit Mobil di PT Clipan Finance Indonesia Dengan Metode Simple Additive Weighting (SAW) - Yan Mitha Djaksana (Institut Sains dan Teknologi Nasional, 2023)
Abstract PT Clipan Finance Indonesia is a car loan financing leasing company. This company has a standard in determining whether or not a customer is eligible for car loan financing. In choosing clients who deserve for car loan financing, it must be done properly to avoid client credit congestion, so it is necessary to select client data analysis. In selecting this client data, a decision support system information was designed that can help determine the priority of clients who are eligible for car loan financing, by using the Simple Additive Weighting (SAW) method as a method of supporting decision making. The SAW method is used to support decision making to evaluate the feasibility value of clients in selecting data for clients who apply for car loans based on the criteria and weight of decision making. Through this system, it is hoped that it can help determine the feasibility of applying for a client's car loan more effectively and efficiently by making the ranking value obtained as a reference for determining client creditworthiness approval. Keywords: Car Loan Financing, Decision Support System, Simple Additive Weighting